Characterization of a Novel Oxidative Stress Responsive Transcription Regulator in Mycobacterium bovis - Qiang Jiang; Rong Hu; Feng Liu; Feng Huang; Lei Zhang; Hua Zhang (Biomedicines, 2024)
The antioxidant defense is critical for the survival of intracellular pathogens such as Mycobacterium tuberculosis complex (MTBC) species, including Mycobacterium bovis, which are often exposed to an oxidative environment caused by reactive oxygen species (ROS) in hosts. However, the signaling pathway in mycobacteria for sensing and responding to oxidative stress remains largely unclear. In this study, we characterize a TetR-type transcription regulator BCG_3893c, designated AotM, as a novel redox sensor in Mycobacterium bovis that increases mycobacterial tolerance to oxidative stress. AotM is required for the growth of M. bovis in the presence of 1 mM hydrogen peroxide. Loss of the aotM gene leads to altered transcriptional profiles with 352 genes significantly up-regulated and 25 genes significantly down-regulated. AotM recognizes a 14-bp palindrome sequence motif and negatively regulates the expression of a FAD-dependent oxidoreductase encoded by bcg_3892c. Overexpression of BCG_3892c increases intracellular ROS production and reduces the growth of M. bovis. In summary, we propose that AotM enhances the mycobacterial resistance against oxidative stress probably by inhibiting intracellular ROS production. Our findings reveal a novel underlying regulatory mechanism behind mycobacterial oxidative stress adaptation.